An interesting case of subdiagphragmatic cold abscess: a case report - C., Tharun Ganapathy; S., Jeyakumar; Mathew, Koshy; Sekhar, Sidhu (International Surgery Journal, 2018)
Subdiaphragmatic abscess is rather common itself but a tubercular subdiaphragmatic abscess in the absence of coexisting tuberculous abdomen presenting as thoracic complication is extremely rare. A cold abscess is an abscess that commonly accompanies tuberculosis. It develops so slowly that there is little inflammation and it becomes painful only when there is pressure on the surrounding area. Here we report a case of isolated subdiagphragmatic tuberculous cold abscess in a 38-year-old female whose imaging of the abdomen revealed a hyperechogenic area involving segment 7 of liver adherent to rib cage and diaphragm, S/O ruptured liver abscess, subdiagphragmatic abscess. The pus drained from the abscess cavity at diagnostic laparoscopy proved Multidrug Resistant Tuberculosis. This case has been reported for the rarity of isolated subdiaphragmatic tuberculous abscess and the importance of microscopic or culture diagnosis in a suspected case of tuberculous abscess.